1998
DOI: 10.1136/gut.42.5.715
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered hepatic matrix degradation in genetic haemochromatosis

Abstract: Background-Altered matrix degradation contributes to fibrosis in some liver diseases but the role of matrix degradation in fibrogenesis associated with genetic haemochromatosis has not previously been addressed. Conclusions-This study provides the first evidence of an alteration in matrix degradation in haemochromatosis that may be a contributing factor to hepatic fibrogenesis in this disease. Aims-To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…(86,87,121,139) Other novel serum-based assessments of fibrosis have also been reported but have yet to be validated in the clinic. (138,140) There is an emerging role for the use of magnetic resonance imaging (MRI) as an accurate, non-invasive measurement of hepatic iron content and the possible detection of fibrosis. There is a high correlation between the mean liver proton transverse relaxation rates measured using MRI and the biochemical liver iron content.…”
Section: Key Developments In Hfe-hhmentioning
confidence: 99%
“…(86,87,121,139) Other novel serum-based assessments of fibrosis have also been reported but have yet to be validated in the clinic. (138,140) There is an emerging role for the use of magnetic resonance imaging (MRI) as an accurate, non-invasive measurement of hepatic iron content and the possible detection of fibrosis. There is a high correlation between the mean liver proton transverse relaxation rates measured using MRI and the biochemical liver iron content.…”
Section: Key Developments In Hfe-hhmentioning
confidence: 99%
“…66 A recent study has demonstrated that patients with hemochromatosis and hepatic fibrosis have increased ratios of TIMP‐1 compared to either collagenase‐1, gelatinase A, or stromelysin‐1. 67 In patients with chronic hepatitis C treated with interferon, responders had an increase in serum collagenase‐1 and a decrease in serum TIMP‐1; nonresponders had the reverse effect, suggesting that interferon may exert a beneficial effect on hepatic fibrosis. 68…”
Section: Serum Mmps and Timps In Liver Diseasementioning
confidence: 99%
“…[32][33][34] They showed this to be an iron oxidase located on the basolateral surface of the enterocyte that is required for efficient iron export by ferroportin. 35,36 Grant Ramm focused on ferritin trafficking pathways, 37-39 hepatic stellate cell biology and hepatic fibrosis, [40][41][42] and matrix synthesis and degradation 43,44 and, more recently, on ferritin as a proinflammatory cytokine. 45 Our work on disrupted hepcidin regulation in HFE-associated HH 46 showed, for the first time, that HFE acts as a regulator of hepcidin expression in the liver, rather than being a hepcidin target as previously proposed (Fig.…”
Section: International Influencementioning
confidence: 99%